Assessment of Vitamin D Deficiency in Patients Presenting with Osteoarthritis in a Tertiary Care Hospital (Medical Forum Monthly, 2020)
Objective: To measure the frequency of Vitamin D deficiency in those patients who are presenting with osteoarthritis in a tertiary healthcare unit.Study Design: cross sectional (single center) studyPlace and Duration of Study: This study was conducted at the General Medicine department at Liaquat National Hospital Karachi from July 2018 to Dec 2018.Materials and Methods: Two hundred osteoarthritis patients were put into the inclusion criteria of this study. Then venous blood sample of each patient was obtained by using 5cc BD syringe. Samples were then sent to the hospital`s laboratory for assessment of level of vitamin D in blood. All procedures were noted on proforma.Results: The mean age of the respondents came out to be 57.57±9.91 years. There were 121(60.5%) male and 79(39.5%) female. Vitamin D deficiency`s frequency in patients presenting with osteoarthritis was observed in 56% (112/200) patients.Conclusion: High percentage of deficiency of vitamin D was revealed. Vitamin D deficiency`s frequency increased significantly with increasing age and was found to be greater in female patients. It is needed to take instant measures for tackling this increasing public health issue.